Terminology for cone dimensions after local conservative treatment for cervical intraepithelial neoplasia and early invasive cervical cancer: 2022 consensus recommendations from ESGO, EFC, IFCPC, and ESP - Kyrgiou, Maria; Athanasiou, Antonios; Arbyn, Marc; Lax, Sigurd F; Raspollini, Maria Rosaria; Nieminen, Pekka; Carcopino, Xavier; Bornstein, Jacob; Gultekin, Murat; Paraskevaidis, Evangelos (The lancet oncology, 2022)
Local cervical treatment for squamous intraepithelial lesion (SIL) or cervical intraepithelial neoplasia (CIN) removes or ablates a cone-shaped or dome-shaped part of the cervix that contains abnormal cells. This Series paper introduces the 2022 terminology for cone dimensions after local conservative treatment for SIL, CIN, or early invasive cervical cancer. The terminology was prepared by the Nomenclature Committee of the European Society of Gynaecologic Oncology, the European Federation for Colposcopy, the International Federation of Cervical Pathology and Colposcopy, and the European Society of Pathology. Cone length should be tailored to the type of transformation zone. Treatment of SIL or CIN is associated with an increased risk of preterm birth, which escalates with increasing cone length. There is a lack of agreement regarding terms used to report excised specimen dimensions both intraoperatively and in the pathology laboratory. Consensus is needed to make studies addressing effectiveness and safety of SIL or CIN treatment comparable, and to facilitate their use to improve accuracy of antenatal surveillance and management. This Series paper summarises the current terminology through a review of existing literature, describes new terminology as agreed by a group of experts from international societies in the field of cervical cancer prevention and treatment, and recommends use of the new terminology that will facilitate communication between clinicians and foster more specific treatment guidelines that balance obstetrical harm against therapeutic effectiveness.